Cover Feature: Programmed Synthesis of Molecular Wires with Fixed Insulation and Defined Length Based on Oligo(phenylene ethynylene) and Permethylated α‐Cyclodextrins (Chem. Eur. J. 60/2017). Issue 60 (30th August 2017) - Masai, Hiroshi; Fujihara, Tetsuaki; Tsuji, Yasushi; Terao, Jun
Abstract : Mother and child play toy trains, they freely arrange the sequences of containers. This image describes a new synthetic method of insulated molecular wires with strictly defined axle lengths and macrocyclic covering positions/degrees. A completely insulated molecular wire (up to a linked‐[11]rotaxane) was afforded through an iterative synthetic technique. Moreover, the insulated areas were selectively controlled using programed solvent conditions. More information can be found in the Full Paper by J. Terao et al. onpage 15073 .